Towards Automatic Modelling of Requirements - Meziane, Farid; Vadera, Sunil (Malaysian Journal of Computer Science, 2017)
The first phases of the FORSEN system that helps the analyst to use an informal specification as the basis of producing a formal specification and concerns the modelisation of the requirements into entity relationship models (ERM) is described. The modelisation is done from the logical form expressions obtained from the analysis of the natural language text. The ERM models are then used as a basis for the production of formal specification in the Vienna Development Method (VDM).